ANALISIS KIMIA KAYU NANGKA (Artocarpus heterophyllus lamk) DARI JAWA BARAT (chemical analysis of jackfruit wood from west java) - Sri Komarayati; Poedji Hastoeti (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
Jackfruit plant (artocarpus heterophyllus lamk) is know as multipurpose tree. A chemical analysis of jackfruit wood from west java has been conducted to determine the contents of cellulose, lignin, pentosan,ash,silica and solubility in cold water, hot water, one percent sodium hydroxide and alcohol-benzene (1:2).The results showed that cellulose content 56,47 percent, lignin 28,76 percent, pentosan 18,64 percent, ash 0,78 percent, and silica 0,37 percent. Thesolubility in cold water 12.29 percent, hot water 14,41 percent, one percent sodium hydroxide 24,70 percent, and solubility in alcohol-benzene (1:2) 10,78 percent.